2012
DOI: 10.3989/mc.2012.07111
|View full text |Cite
|
Sign up to set email alerts
|

Comportamiento de Sistemas Provisionales de Protección de Borde de polietileno de alta densidad frente a cargas estáticas y de impacto

Abstract: We have tested under static and dynamic load temporary edge protection systems (TEPS) formed by a continuous fence, some are made of high density polyethylene (HDPE) and others have been manufactured using a composite material, adding glass fiber at a matrix of HDPE at a rate of 4%.Tests under static and impact have been performed according to standard UNE-EN 13374, class systems A and B. It has been found the influence of aging on TEPS and samples of the same materials as the TEPS.All tested TEPS exceed the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Based on these results, plastic materials are discarded due to their low performance in bending tests. On the contrary, previous studies analysed the high-density polyethylene (HDPE) materials to be applied but in surface (non-linear) elements [62]. Likewise, both the reference material and cast iron and carbon-fibre-reinforced polymer are postulated as good candidates for the next stage of the study.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these results, plastic materials are discarded due to their low performance in bending tests. On the contrary, previous studies analysed the high-density polyethylene (HDPE) materials to be applied but in surface (non-linear) elements [62]. Likewise, both the reference material and cast iron and carbon-fibre-reinforced polymer are postulated as good candidates for the next stage of the study.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Systems: There is a wide variety of collective protection systems available on the market for the construction sector, such as systems embedded in the concrete in plastic cartridges inserted into slabs, jaw-type posts tightened in concrete structures or fixed to metal profiles, clamp-type posts that can be fixed onto a wide range of slab edges, integrated safety systems used in the execution of formwork, telescopic vertical struts, V-type safety nets, etc. Likewise, within these systems, there are railings, nets, plinths and wire mesh which cover the gaps through which falls can occur, as well as anchoring systems, including flanges and uprights, with specific designs for their coupling; • Materials: The most commonly used material for the manufacture of railings and uprights is galvanised steel [59], although other types of material such as aluminium [60], wood [61] or high-density polyethylene (HDPE) [62] can also be found, among others.…”
mentioning
confidence: 99%
“…The influence of aging has been studied on TEPS made with HDPE and subjected to natural ageing. (González, Cobo, Lozano & Bresó, 2013). The continuous fence is formed by three horizontal elements, 150 mm in height, two vertical elements at the edges, and diagonal elements 200 mm wide with intermediate spaces located at the top and bottom rectangular spaces.…”
Section: Teps Made Of High Density Polyethylene (Hdpe)mentioning
confidence: 99%
“…Moreover, a number of studies have shown that a TEPS is an excellent collective protection system that prevents a substantial number of falls from height accidents [17][18][19][20]. However, several static load and impact studies evaluating the performance of several TEPS [21][22][23][24][25][26] have found certain conventional TEPS failed to meet the international standards and specifications on the geometric and dynamic requirements of TEPS [27][28][29][30][31]. It should be noted that these standards and specifications vary considerably worldwide [32].…”
Section: Introductionmentioning
confidence: 99%